STRATEGY TO FIGHT COVID-19: ACCESS TO VACCINATION FOR PEOPLE AGED > 65 IN RWANDA - RWABIHAMA, Pr. Jean-Paul; RWAGASORE, E.; SIBOMANA, H.; SAYINZOGA, F.; MUTESA, L.; DUGUET, A.-M. (MEDECINE LEGALE DROIT MEDICAL, 2025)
Rwanda has developed a dynamic strategic plan to fight Covid-19 pandemic centered on preventive public health measures and the accessibility to vaccination for population groups with high risk, especially: for people aged > 65. The priorization of this group is a considerable step forward in improving acces to health care for vulnerable populations in this context of health crisis where the ethics of equity supports the ethics of urgency. In a pyramidal system of healthcare access, the priorization of this vulnerable population group for vaccination against Covid-19, could be extended to all health care and thus allows early management of chronic diseases of this aged population.